The Mechanical properties and statistical analysis of the Charpy impact test using the Weibull distribution in jute-polyester and glass-polyester composites (Fracture and Structural Integrity, 2022)
In recent years, the use of natural fiber composites to provide a possible replacement for synthetic fiber composites for practical applications has been the subject of several studies. This study deals with the fabrication and investigation of jute-polyester composites and the comparison of it with glass-polyester composites. The static mechanical properties of the composites is obtained by testing the composite lamina for tensile and ﬂexural strength. The dynamic mechanical properties of the composites is determined by using the Charpy impact test. By the Williams method based on the principle of linear elastic fracture mechanics, the impact toughness of the composites is deduced. The experimental results were statistically analyzed by using the Weibull theory to better understand the impact behavior of the composites. It is found that the glass-polyester composite has better properties than the jute-polyester composite.
Keywords: Jute; Glass; Polyester; Statistically analyzed; Impact strength